2020
DOI: 10.1186/s13643-020-01548-7
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-based interventions for children and adolescents across all settings: a scoping review protocol

Abstract: Background and purpose Although mindfulness-based interventions (MBIs) are becoming increasingly popular, the application of MBIs with children and adolescents is still in its infancy. Mapping the existing literature is necessary to help guide pediatric mindfulness interventions. Our purpose is to synthesize the evidence of reported MBIs for children and adolescents with and without physical, mental, and cognitive disorders. Accordingly, we aim to identify trends and gaps in the literature, so … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The potential various beneficial effects of mindfulness among school children have been examined in several studies (Dunning et al, 2019;Hayes et al, 2019;Kallapiran et al, 2015aKallapiran et al, , 2015bKuyken et al, 2017;Perrier et al, 2020) but studies focusing solely on symptoms of depression and anxiety are still sparse and evidence is contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…The potential various beneficial effects of mindfulness among school children have been examined in several studies (Dunning et al, 2019;Hayes et al, 2019;Kallapiran et al, 2015aKallapiran et al, , 2015bKuyken et al, 2017;Perrier et al, 2020) but studies focusing solely on symptoms of depression and anxiety are still sparse and evidence is contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…Meta‐analyses support the effectiveness of mind–body approaches for improving mental and physical health in the general population (Feruglio et al, 2022; Perrier et al, 2020; Section on Integrative Medicine, 2016). For example, data from 209 mindfulness‐based therapy trials indicated moderate effectiveness compared to no intervention and other active treatments, including psychological treatments, for anxiety, depression, and stress, with efficacy comparable to that observed for cognitive behavioral therapy and antidepressants (Khoury et al, 2013).…”
Section: Mind–body Interventions: the “What” “How” And “Why”mentioning
confidence: 99%
“…Research into MBIs and relaxation-based interventions has grown exponentially in the last two decades, due in part to their relatively low-cost and ease of delivery (Perrier et al, 2020). Some of the most common techniques, which are often paired together in multi-modal intervention programmes, are detailed in brief below.…”
Section: Relaxation-based Interventionsmentioning
confidence: 99%